1991
DOI: 10.1177/0013916591234005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Household Recycling Behavior

Abstract: To investigate factors encouraging or deterring recycling, telephone interviews were used to study recycling behavior, attitudes, and knowledge of 221 randomly selected adults in a suburban city that had begun a citywide curbside recycling program within the past year. Approximately 40% reported participation in the curbside recycling program, and nearly 20% more claimed that their household had been recycling in other ways. Most demographic variables did not predict participation in the curbside recycling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
407
3
10

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 689 publications
(458 citation statements)
references
References 26 publications
30
407
3
10
Order By: Relevance
“…The authors pointed out that householders may not recycle due to the sheer effort required to overcome high personal barriers. Similarly, Vining and Ebero [80] and Oskamp et al [89] reported time to be a major effort and important inconvenience factor in performing recycling behaviour, while economists also underline the high opportunity cost of time in their studies [38]. Conversely, only Hornik et al [7] do not report any significant dependence between personal effort and recycling behaviour.…”
Section: Socio-psychological Group Of Variablesmentioning
confidence: 95%
“…The authors pointed out that householders may not recycle due to the sheer effort required to overcome high personal barriers. Similarly, Vining and Ebero [80] and Oskamp et al [89] reported time to be a major effort and important inconvenience factor in performing recycling behaviour, while economists also underline the high opportunity cost of time in their studies [38]. Conversely, only Hornik et al [7] do not report any significant dependence between personal effort and recycling behaviour.…”
Section: Socio-psychological Group Of Variablesmentioning
confidence: 95%
“…It has been argued that higher levels of environmentally relevant knowledge play a significant role in modifying environmental behavior [33,34]. Schahn and Holzer [35] follow two definitions of knowledge in their research on recycling: abstract knowledge (AK), which focuses on awareness of general environmental issues, and concrete knowledge (CK), which evaluates awareness of local services, for example, recycling services [36].…”
Section: Introductionmentioning
confidence: 99%
“…A positive relationship between attitudes and behavior has been indicated in some cases (Kallgren and Wood, 1986;McGuiness et al, 1977;Tilikidou, 2001), whilst no relationship was found in others (Ebreo and Vining, 1994;Oskamp et al, 1991). However, there is an agreement in the literature that specific recycling attitudes are better predictors than are general pro-environmental attitudes (Martin and Siminitras, 1995;Schlegelmilch et al, 1996;Shrum et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%